Clinical and Histopathological Features of Primary Oral Cancers in Shiraz, Iran: A 7- Years Retrospective Study - Daneste , Hossein; Jamshidi , Ladan; Maroufi , Sara; Sadeghzadeh , Azita; Moayedi , Javad (Galen Medical Journal, 2024)
Background: This study aimed to assess the clinical and histopathological factors associated with primary oral cancer in Shiraz, southwest Iran. Materials and Methods: This retrospective cross-sectional observational study evaluated 100 patients with primary oral cancers at the Department of Oral and Maxillofacial Medicine of Shiraz University of Medical Sciences between January 2014 and December 2020. Data were collected from patient records, including age, sex, occupation, family history, spice use, smoking history, alcohol consumption, underlying diseases, lesion location, pathology grade, TNM stage, perineural invasion, time of diagnosis, number of surgeries, and history of radiotherapy and chemotherapy. Results: The average age of patients was 58.5±9.2 years (range 40-70 years), with 67% being men. Smoking, alcoholism, systemic diseases, spice use, and family history were present in 46%, 32%, 32%, 11%, and 11% of patients, respectively. Lymph node involvement was observed mostly in zone I (99%). The mandible was the most commonly affected site (46%), followed by the tongue (39%), buccal mucosa (23%), maxilla (20%), oral floor (18%), lower lip (7%), and upper lip (1%). Squamous cell carcinoma (SCC) accounted for 97% of cases, with other primary oral malignancies comprising the remaining 3%. Among the neoplasms, 55% were well-differentiated, while 45% were moderately differentiated. Conclusion: This study found that primary oral malignancies in Shiraz, Iran were predominantly found in men, with smoking and systemic diseases being major risk factors, and identified the mandible and tongue as the most common sites, with SCC being the most prevalent pathology, often well-differentiated.